Da'wah Management of Wali Songo in the Age of Majapahit Kingdom - Novrida Qudsi Lutfillah (Yayasan Rumah Peneleh, 2019)
The purpose of this research is to trace the da'wah management conducted by Wali Songo broadcasting Islam in Java, especially at the Majapahit Kingdom. The method used literature study, in which the researcher is the main instrument that will read the literature and more emphasized on the process because history and literary philology are rich with interpretation. The results show that Wali Songo as da'wah organization, has method and management of da'wah that combines local culture in Majapahit by still upholding Islamic values.